2016
DOI: 10.1038/srep36304
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional changes during ovule development in two genotypes of litchi (Litchi chinensis Sonn.) with contrast in seed size

Abstract: Litchi chinensis is a subtropical fruit crop, popular for its nutritional value and taste. Fruits with small seed size and thick aril are desirable in litchi. To gain molecular insight into gene expression that leads to the reduction in the size of seed in Litchi chinensis, transcriptomes of two genetically closely related genotypes, with contrasting seed size were compared in developing ovules. The cDNA library constructed from early developmental stages of ovules (0, 6, and 14 days after anthesis) of bold- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 99 publications
5
7
0
Order By: Relevance
“…The Glyma.03G029800.1 gene was identified as GmYABBY5, which helps maintain meristems during the early floral developmental stages (Zhao et al, 2017). The Arabidopsis homolog of this gene is AT2G45190, which mediates biological processes related to ovule, embryo, and flower development (Lenser et al, 2016;Pathak et al, 2016). In tomatoes, the YABBYlike transcription factor was also found to play a pivotal role in fruit size regulation (Cong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Glyma.03G029800.1 gene was identified as GmYABBY5, which helps maintain meristems during the early floral developmental stages (Zhao et al, 2017). The Arabidopsis homolog of this gene is AT2G45190, which mediates biological processes related to ovule, embryo, and flower development (Lenser et al, 2016;Pathak et al, 2016). In tomatoes, the YABBYlike transcription factor was also found to play a pivotal role in fruit size regulation (Cong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For eight genes, five candidate genes were detected in the NThSP03-1 interval (i.e., Glyma.03G026100.1, Glyma.03G026300.1, Glyma.03G026400.1, Glyma.03G026900.1, and Glyma.03G029800.1). The homologous genes in the soybean genome were Glyma.01G140600.1 and Glyma.17G138200.1 (Zhao et al, 2017;Chen et al, 2018), whereas the homologous genes in the Arabidopsis genome were AT1G71820 and AT2G45190 (Nolan et al, 2009;Lenser et al, 2016;Pathak et al, 2016). Based on previous studies, functional characterization of these genes indicated that they are involved in pollen germination; pollen tube growth; meristem growth; ovule, embryos, flower, and fruit development; and cell division.…”
Section: Candidate Gene Predictionmentioning
confidence: 98%
“…The two genotypes with contrasting seed size are genetically fairly close (Nei genetic distance of 0.46) (Pathak et al 2014) as compared to the other popular cultivars in India and grouped in the same cluster as the previously reported litchi transcriptome genotypes. Developing fruits at 16, 20, 24 and 28 days after anthesis (DAA) were harvested, dipped in liquid N 2 , and stored in -80 o C (Pathak et al 2016). Seeds were excised from the stored fruits and total RNA was isolated, using Spectrum Plant Total RNA kit (Sigma Aldrich St. Louis, MO, USA), following manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Relative expression of Trinity transcripts among RNAseq libraries from two litchi genotypes at four seed developmental stages was obtained as TPM (transcripts per million) and FPKM (fragments per kilobase of transcripts per million mapped reads), using RSEM version 1.2.9 at default parameters (Pathak et al 2016). Expression levels of different Trinity transcripts were compared among the samples by Edger Bioconductor, using script run_DE_analysis.pl as default parameter.…”
Section: De-novo Reference Assembly and Prediction Of Transcript Expr...mentioning
confidence: 99%
See 1 more Smart Citation